A survey on resource sharing among libraries in Bogor area, Indonesia - Hidayat W., Sjarif; Hidalgo, Namnama P.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1986)
The purpose of this study is to describe the nature and prospects of resource sharing activities among agriculture-based libraries in Bogor area, Indonesia, and to identify the problems and factors that hinder or enhance resource sharing among them.
A survey was conducted using a questionnaire to gather data from 24 libraries in Bogor. The questionnaire elicited answers on the nature of resource sharing in terms of collections, policies, facilities, library services, communication media, technical processing and attitude of the respondent librarians.
The findings revealed that the agriculture-based libraries in Bogor area covered the subject fields soil science, agro-based industry, botany, animal science, biology, fisheries, estate crops, food crops, medicinal plants, nutrition and forestry. The special collections of these libraries are comprised mainly by research reports, internal reports and theses/dissertations done by their staff and scientists. The libraries are engaged in resource sharing activities, particularly interlibrary loan and staff training. Furthermore, provision of photocopies of materials/articles is more popularly carried out by the libraries instead of lending out books.
The respondent librarians have positive attitudes towards resource sharing. They agree that resource sharing activities must be developed for efficient and effective service. However, some problems hinder participation in resource sharing: prohibitive library regulation, inadequate bibliographic tools, organizational policies of mother institutions, inadequate trained and capable manpower to run the resource sharing activities and some libraries do not have bibliographic tools and the librarians have difficulty in finding and locating needed materials. Also, some libraries do not have good communication facilities (telephone). It is often difficult to contact the librarians directly without considerable waiting time.
The positive attitudes of the librarians towards resource sharing, the absence of personality conflicts among library personnel, intensive library development planning and implementation of networking since 1972, and the role of NLAS as the national focal point for library and agricultural information provide a healthy environment for the further development and intensification of resource sharing activities not only among the libraries in Bogor area but all over Indonesia.
A Bogor library consortium committee should be established to formulate rules and procedures regarding resource sharing and to promote and maximizing information networking. On-going production of union list and catalogues and manpower training should be intensified. New information technology should be adopted to facilitate cooperative activities and improve the efficiency and effectivity of services to Indonesia scientists and other users of information.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library cooperation -- Indonesia -- Bogor